Implementasi Kebijakan Pemerintah Kota Surabaya Dalam Mewujudkan Inovasi Smart City - Devi Novita Sari; Dia Zulfia Rahmadani; Mohamad Yusuf Wardani (Journal of Governance Innovation, 2020)
Government policy in the formation of smart cities in the city of Surabaya is an embodiment of the implementation of e-government programs. With this regional innovation, it will aim to improve the performance of local governments. The target of regional innovation must be directed to accelerate the realization of welfare in society by improving the quality of public services. The purpose of this study is to determine the differences in the potential of each region will affect where the concept of smart city will be built, both from differences in natural resource factors, and human resources. This research method uses descriptive qualitative research using a literature study approach. The indicators in determining the success of Surabaya City Government's policy in realizing smart city are examined using Edward III's implementation theory. The results of research through 4 studies of the implementation concept of Edward III, the Surabaya City Government in carrying out the implementation of the policy can be said to be successful, the success of the implementation of the Surabaya City Government's policy can be proven by the Surabaya City Government through the efforts made in realizing Smart Government, Smart Economy, Smart Environment, Smart Living , Smart People, and Smart Mobility.